Development of the algal pigment-based salinity transfer function for lakes on the Tibetan Plateau and evaluation of the quantitative reconstruction - Xinyao Sun; Qi Lin; Chenliang Du; Shixin Huang; Ke Zhang; Ji Shen (Ecological Indicators)
Recent limnic environment on the Tibetan Plateau is fluctuating dramatically due to anthropogenic warming, significantly affecting primary producers and the stability of aquatic ecosystems. Fossil pigments in lake sediments have been widely used to track the response process of algae communities to climatic and environmental changes, but their potential in quantitative reconstructions is rarely explored, particularly in remote mountains with monitoring data scarcity. Here, the relationship between water environmental variables and surface sediment pigment assemblage identified by high-performance liquid chromatography (HPLC) covering 95 Tibetan lake sampling sites was investigated based on multivariate statistical analysis. Salinity was considered as the most important factor determining the distribution pattern of pigment assemblage, and pigment concentrations differed significantly along the lake salinity gradient. Nine chlorophyll, xanthophyll and carotenoid pigments were comprehensively assessed to develop the pigment-salinity transfer function. Sedimentary pigment preservation and salinity range have been taken into consideration, and locally weighted weighted average (LWWA, R2 = 0.74, RMSEP = 0.99 g/L) and locally weighted weighted average partial least squares (LWWAPLS, R2 = 0.74, RMSEP = 0.95 g/L) were identified as the best performing models. The pigment-based transfer function was applied to quantitatively reconstruct the salinity of Haidingnuoer Lake salinity on the northeastern Tibetan Plateau over the past 150 years, and the reliability and robustness of the reconstruction was verified. Comparison with other paleoclimatic and meteorological records revealed that the lake salinity was mainly influenced by climate-mediated changes in regional precipitation and effective moisture. This study established a new algal pigment-based salinity transfer function, and provided a promising indicator and method to quantitatively reconstruct past lake environmental conditions on the Tibetan Plateau.